Continuous flow hydrogenations using novel catalytic static mixers inside a tubular reactor. Issue 2 (3rd January 2017) - Avril, A.; Hornung, C. H.; Urban, A.; Fraser, D.; Horne, M.; Veder, J.-P.; Tsanaktsidis, J.; Rodopoulos, T.; Henry, C.; Gunasegaram, D. R.
Abstract : Continuous flow reactor for the hydrogenation of organic substrates using novel catalytic static mixers. Abstract : This work describes a novel continuous flow reactor concept for organic synthesis using heterogeneous catalysts. The concept is based on static mixers coated with a catalytic metal layer, which can be inserted into standard stainless steel reactor tubing. The static mixers were prepared by 3D metal printing, allowing for maximum design flexibility and thus can be tailored to a large number of chemical synthesis applications. The nickel or platinum catalysts were deposited either by metal cold spraying or electrodeposition, which allows for potential scale up and mass production and these techniques are compatible with a range of different catalytic metals. The catalytic flow reactor was evaluated for a series of continuous flow hydrogenations of alkenes and carbonyls.